Парофазне окиснення пропіленгліколь-метанольної суміші до метиллактату на СeO2/Al2O3каталізаторі - Sharanda, Mykhailo E.; Mylin, Artur M.; Zinchenko, Oleksii Yu.; Brei, Volodymyr V. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2023)
The vapor-phase oxidation of mixtures of propylene glycol with methanol and ethanol to methyl and ethyl lactate, respectively, on supported CeO2/Al2O3 catalyst at 210-2500С was investigated. Air oxygen and a flow reactor with a fixed catalyst bed were used. A 20% solution of propylene glycol in alcohol was supplied to the reactor inlet. Oxidation of propylene glycol in the presence of methanol occurs according to the overall reaction CH3CHOHCH2OH +O2 + СН3OH = CH3CHOHCOOСН3 +2H2O. First, hydroxyacetone is formed, which is further oxidized to pyruvic aldehyde, which adds alcohol to form a hemiacetal. Next, this hemiacetal is rearranged according to Cannizzaro into methyl lactate. At 2200C and catalyst load < 2 mmol PG/gcat/h, the selectivity for methyl lactate reached 70 wt.% at 100% propylene glycol conversion. In the presence of ethanol, the formation of a significant amount of acetaldehyde and its aldol condensation products, as well as the formation of diethoxyethane, was observed. Therefore, the selectivity for ethyl lactate at 100% propylene glycol conversion did not exceed 45%.